2004
DOI: 10.1038/sj.jp.7211171
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Health-Care Providers towards Research with Newborn Babies

Abstract: CONTEXT:By providing information and possibly shaping parents' preferences, health-care providers are thought to play a critical role in parental decisions to enroll their infants in research. Yet, little is known about health-care providers' beliefs about research with newborns. Previous studies suggest that parents and health-care providers are often at odds regarding attitudes towards research. OBJECTIVE:To examine the attitudes of health-care providers concerning the acceptability of research with newborn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…Limited research has shown that nurses generally have positive attitudes towards pediatric research but are reticent to recommend participation to their patients, due to a lack of understanding about clinical research, lack of familiarity with a specific trial or disapproval of the research question. (9, 11, 18) Our findings may help other study teams understand the potential impact of bedside nurses' attitudes on the planning and execution of complex multi-institutional studies.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Limited research has shown that nurses generally have positive attitudes towards pediatric research but are reticent to recommend participation to their patients, due to a lack of understanding about clinical research, lack of familiarity with a specific trial or disapproval of the research question. (9, 11, 18) Our findings may help other study teams understand the potential impact of bedside nurses' attitudes on the planning and execution of complex multi-institutional studies.…”
Section: Discussionmentioning
confidence: 81%
“…However, pediatricians are often reluctant to refer their patients for research studies (5, 6) due to potential risks from treatment side effects, patient inconvenience, lack of physician time/resources and risk to the doctor-patient relationship. (7-9)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Administrative challenges (multiple Institutional Review Board [IRB] approvals, subcontracts, and training), scientific challenges (equipoise and standardizing protocols among various centers) and financial challenges are common in multi-site trials (1, 2). These are compounded when pediatric researchers must identify eligible research subjects from smaller pediatric patient pools compared with adult trials, address complex issues of parental consent and child assent (3, 4), tackle the perceptions and lack of understanding among parents and pediatric healthcare providers about research with children (57), manage the range of IRB assessments of trial risks and benefits (4, 8, 9), and procure the requisite expertise and additional funds needed to perform study interventions and long-term follow-up in children (10). Strategies have been identified for simplifying research processes, streamlining activities and decreasing the often-excessive time required to complete a trial (1114), yet investigators continue to struggle to complete recruitment on time and within the budget allotted (15, 16).…”
Section: Introductionmentioning
confidence: 99%
“…Surveys show that nurses, doctors, and ancillary personnel might be unaware of studies for which their patients may be eligible and while largely supportive of pediatric research, express concern about how informed families are. They also acknowledge that it creates a burden and takes time to talk with parents about research, a topic about which they themselves may know little (8-10). …”
mentioning
confidence: 99%